Communication Media for the Indonesian Malay Cultural Traditional Council in Strengthening Politics in Langkat Regency - Ahmad Muhajir; Zainun, Zainun; Efi Brata Madya (Dinasti Research, 2024)
This study aims to analyze: (1) Analyzing What Communication Media are Used by the Indonesian Malay Culture Council in Strengthening Politics in Langkat Regency. (2) Activities and Da'wah Activities of the Indonesian Malay Culture Council in Strengthening Politics in Langkat Regency. (3) Communication Barriers Faced by the Indonesian Malay Culture Council in Strengthening Politics in Langkat Regency. This study uses descriptive methods and a qualitative approach. Using a qualitative approach, also known as the Naturalistic method, as this research is conducted in a natural setting. The results of the study show that the Communication Media used by the Indonesian Malay Culture Council in strengthening politics in Langkat Regency includes various communication media such as Interpersonal Media, Mass Media, and Social Media. The Da'wah activities of the Indonesian Malay Culture Council in strengthening politics in Langkat Regency encompass a variety of activities aimed at strengthening Malay cultural values ??and increasing political participation and awareness, including Da'wah Bil Kitabah, Da'wah Bil Lisan, and Da 'Wow Bill Hal. Communication barriers faced by the Indonesian Malay Culture Council include Technical Barriers, Semantic Barriers, and Human Barriers.